Coen’s ascending ramus fixator use for repositioning the ascending ramus during mandible reconstruction - Coen Pramono D (Dental Journal (Majalah Kedokteran Gigi), 2008)
The aim of mandible reconstruction using reconstruction plate after resection is to restore aesthetic and function for muscles attachment and allow mandible movement during normal function and free from joint problem. Temporomandibular joint (TMJ) is an area of concern during mandible reconstruction using reconstruction plate as misalignment on placing of the reconstruction plate may cause the joint place in distortion to the glenoid fossa. Loss large part of mandible bone structure may lead problems during mandible reconstruction procedure because the surgeon may lose in orientation during forming the reconstruction plate into a horseshoe-shaped form of the mandible as well as during plate placement. The plate can only be well adapted when the position of two distal ends of the resected mandible bone are in a stable position. Simple ascending ramus fixator (CARF) to fix the ascending ramus in its stable original position to allow easy mandible reconstruction was created. Those CARF were designed in two types which have one and two fixator stems used to stabilize one or both sites of the ascending rami and showed its effectiveness.